ANALISIS PEMAHAMAN KONSEP HIMPUNAN MAHASISWA DITINJAU DARI ASAL SEKOLAH - Sudirman (Universitas Wiralodra, 2016)
The purpose of this research is (1) analyze student?s concept in answering the association test, (2) analyze the concept of understanding  relationship  to  answer  the test depends on the student?s school origin.The method used in this research is qualitative with case study approach. In clustering sampling technique the subject was used in this research is 6 students, shared  in  3  groups.  They  are  2  students come from public vocational school, 2 students come from public senior high school and 2 students come from private senior high school and vocational school. Data was collected through test and interview.   Data   analysis   used   in   this research refers to Milles and Huberman in Moellong?s book; they are data reduction, data display and conclusion drawing. The result showed that the student?s understanding is various enough in answering the  set  test.  Depending on  the first subject analysis (S1) who came from private school, he did not understand about the concept of set. The second subject analysis (S2) and the third subject analysis (S3)  who  came  from  public  school,  they had understood. But, they need to be careful and patient to avoid the mistakes. The data which  had  gained from deeply interview, showed that the subject analysis (S1), (S2) and (S3) were able to indicate the relationship of school origin with the student?s concept of understanding within answering the set test.